Determinan Perilaku Disfungsional Auditor Dimoderasi Sifat Machivellian - Rizki, Zidni; Tarmizi, Muhammad Irfan; Fisher, Bobby (Jurnal Akuntansi dan Governance, 2024)
Objectives: This study aims to assess the impact of professional commitment, task complexity, and time budget pressure on auditors' dysfunctional behavior, considering Machiavellian traits as a moderating variable.Design/method/approach: Employing an associative quantitative approach, the research gathered data through the distribution of questionnaires to auditors in public accounting firms in the South Jakarta area. Probability sampling, utilizing the Slovin formula, was employed, resulting in 81 eligible respondents. Data analysis utilized the bootstrapping method, facilitated by SmartPLS version 4 software. Results/findings: The results reveal that professional commitment, task complexity, time budget pressure, and Machiavellian traits all exert a significant positive influence on auditors' dysfunctional behavior. Notably, Machiavellian traits only moderate the relationship between task complexity and auditors' dysfunctional behavior. In contrast, professional commitment and time budget pressure are not moderated by Machiavellian traits concerning auditors' dysfunctional behavior.Theoretical contribution: This study contributes to the literature by demonstrating that auditors' dysfunctional behavior is influenced by a combination of internal and external factors, supporting attribution theory.Practical contribution: The study offers insights for public accounting firms to focus on providing attention, supervision, and motivation to auditors, mitigating dysfunctional behavior and enhancing audit quality.LimitationsThis study’s limitations include its execution during peak season, leading to a predominance of junior and senior auditors responding to questionnaires, and a potential shortfall in questionnaire returns.